(untitled) (Contemporary Mathematics, 2024)
The highly dispersive optical solitons with a quadratic-cubic form of self-phase modulation structure are derived. The governing model was reduced to an ordinary differential equation by the traveling wave hypothesis. Subsequently, the Sardar sub-equation method and its modified version are used to locate the soliton solutions. A full spectrum of optical solitons is thus obtained.